Implementation and Impact of RFID in Library Management Systems - Joyson Mascarenhas; Bhausaheb Eknath Shinde (International Journal of Solid State Innovations & Research, 2024)
This system relies on UHF RFID scanners at the gate and transaction section, which are supported by antennas and RFID transceivers embedded in library cards. These devices allow information to be electronically stored and read/written using radio waves without the need for physical interaction. It does not require manual input and instantly sends information about books and library users to the library's management system. It has a record-keeping and search system as well. The recorded module will track every book that passes through the gates in real time, allowing librarians to simply track down and notify anyone who takes a book off the rack without authorization. With the use of an RFID reader, the search module will enable quick book searches. For identification purposes, students will be scanning their ID cards directly. Only those with valid identification are permitted entry into the library. If a librarian is not present, the user can issue or return books immediately after being identified. Information is recorded and transferred to a cloud database whenever a student issues or returns a book. Thus, if a student lends out a book, it is put to his account; if he returns a book, it gets taken out of his name. The library will profit immediately and over time from increased transaction flow, traceability, and security thanks to the library management system.
Keywords: Atmega 328P microcontroller; Automation system; Library Automation; RFID Technology; UHF RFID